Pengaruh Alokasi Dana Desa, Pengeluaran Pemerintah Sektor Pendidikan Dan Kesehatan Terhadap Indeks Pembangunan Manusia Di Provinsi Jawa Timur Tahun 2011-2020 - Almaas Aulia Syah; Aris Soelistyo (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
Investment in human development is seen as a means to increase welfare and sustain economic growth. This study discusses and examines the simultaneous and partial effect of village fund allocations, government spending on education and health sectors on human development which is calculated in the Human Development Index (HDI) of East Java Province in 2011-2020. This study uses multiple linear regression analysis or Ordinary Least Square which explains several variables in the dependent variable. The results of the study found that the allocation of village funds, health and education sector government expenditures in East Java Province had a simultaneous effect on the Human Development Index of East Java Province, while partially the allocation of village funds and health expenditures had an effect on the human development index and education expenditures had no significant effect on human development index